The Effect Of Usability Perception And Easy Perception Of Real Use In Online Purchasing Transactions - Surya Adi Rahman; Fajar Adhitya; Novan Erlandika (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2019)
This study aims to determine instagram users in the needs of product purchase transactions by including variables of perceived usefulness, perceived ease of use, intentin to use and actual usage system. The sample used in this study is Instagram users who have made product purchases through Instagram among Semarang students, the number of respondents is 65 students. This study uses multiple linear regression analysis method. From the results of this study indicate that directly variable perceived usefulness, perceived ease of use influence directly actual usage system and indirectly directly perceived usefulness, perceived ease of ose influence directly to actual usage system through intention to use.